Facile and template-free solvothermal synthesis of mesoporous/macroporous metal–organic framework nanosheets. Issue 58 (24th September 2018) - Zhang, Boce; Luo, Yaguang; Kanyuck, Kelsey; Saenz, Natalie; Reed, Kevin; Zavalij, Peter; Mowery, Joseph; Bauchan, Gary
Abstract : A facile and template-free solvothermal method was developed as a bottom-up approach to synthesize mesoporous/macroporous MOF nanosheets in a simple and scalable way. Abstract : A facile and template-free solvothermal method was developed as a bottom-up approach to synthesize mesoporous/macroporous MOF nanosheets in a simple and scalable way. It was found that starting coordination complexes of different copper(ii )-ligand compounds mediated the controlled growth and morphology of MOF crystals. By controlling the size and shape of the MOF crystals, the possibility to adjust and tailor the structure and performances of the assemblies was demonstrated. This work provides a bottom-up approach to synthesize MOF films and nanosheets in a simple and scalable way, which may have potential in energy and biomedical applications.